The poems : - Shakespeare, William (Cambridge University Press, 1992)
This updated edition of Shakespeare's poems contains a new introductory section on recent critical interpretations. Fully annotated, it includes all the poems which can be confidently assigned to Shakespeare, excluding the Sonnets. An updated reading list completes the edition. --This text refers to an alternate Paperback edition.